RAIDERISM IN LATVIA: ITS CIVIL AND CRIMINAL ASPECTS - Joksts, Jānis (Administrative and Criminal Justice, 2015)
Raiderism is a type of offense that doesn’t have an exact definition in the law system. Author in his publication on the basis of traditional and non-standard raiderism in the country, analyzes the raiderism direction of criminal behaviors which schemes appear in transactions with real estate, as well as transactions relating to situations of economic and financial nature. Furthermore, in the study as raiderism entities are shown physical as well as legal entities. Due to a greater efficiency to combat raiderism, the author comes to the conclusion that the essential role raiderism containment area is attributed to a series of Latvian criminal provisions creativity, as well as the existing provision of substantial amendments and additions to the introduction of the examination raiderism crime phenomenon in every sector of the economy and the public administration institutions.